2018
DOI: 10.1186/s12913-018-3403-4
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and strategies to implement clinical pharmacy services in a metropolis in Northeast Brazil: a qualitative approach

Abstract: BackgroundClinical Pharmacy Services (CPS) are a reality in many health systems around the world. However, there are few studies that discuss the facilitators and the strategies to implement CPS in healthcare systems. In this way, the objective of this study was to identify the facilitators and strategies involved in the CPS implementation process in some public health units in a metropolis in the Northeast Brazil.MethodsA qualitative study was carried out with health-system pharmacists and managers who experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 98 publications
(78 reference statements)
1
26
0
9
Order By: Relevance
“…At the hospital level, potential interaction between doctors and pharmacists and the resulting enhanced collaboration was thought to greatly improve the pharmacist's involvement in patient-centered roles. Similar suggestions have been reported in a US study [55], while a study conducted in Brazil provided evidence that active communication, trust, and respect between pharmacists and physicians promoted improved pharmacy services [32]. However, a Pakistani study also reported that although physicians and nurses consider pharmacists a useful source of information, they regard pharmacist involvement in direct patient care as unpleasant and a menace to hospital harmony [56].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…At the hospital level, potential interaction between doctors and pharmacists and the resulting enhanced collaboration was thought to greatly improve the pharmacist's involvement in patient-centered roles. Similar suggestions have been reported in a US study [55], while a study conducted in Brazil provided evidence that active communication, trust, and respect between pharmacists and physicians promoted improved pharmacy services [32]. However, a Pakistani study also reported that although physicians and nurses consider pharmacists a useful source of information, they regard pharmacist involvement in direct patient care as unpleasant and a menace to hospital harmony [56].…”
Section: Discussionsupporting
confidence: 55%
“…The interview schema was developed through an extensive literature search [30][31][32] and with the aim of answering the research questions. The schema was developed through regular meetings amongst the research team and is outlined in Supplementary File S1.…”
Section: Interview Schema Developmentmentioning
confidence: 99%
“…Table 1 shows the barriers and the categories that emerged from the focus groups and interviews. The facilitator and strategies to implement CPS are described in a previous study [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Factors related to support from the community pharmacy chain were highlighted as facilitators of the implementation process. According to the literature, the support of the institution, the manager, and the supply of training, in uence the provision of CPS in different settings [15,26,27,36]. Regarding autonomy, studies have shown that this factor is in uenced by the market economy, often limiting the capacity for professionals, who are employed, to apply their own judgement when making decisions [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…This data collection method was chosen to include the varied experiences and perceptions of the participants. The interview guide was constructed during a brainstorming meeting between the research team (ARM, KSSR, and SCS), based on relevant literature [25,26,27] and their clinical experiences.…”
Section: Data Collectionmentioning
confidence: 99%